Pengaruh Electronic Word of Mouth, Harga, dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian Pada Social Commerce Tik Tok Shop (Studi Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2019-2020) - Wahyu Sintia; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In the current era of globalization, the internet is a very important need for everyone. In the era of rapid development of information technology, e-commerce has become part of business dynamics. The difference between e-commerce and social commerce lies in business goals, relationships between consumers, and interaction systems. At present there are many social commerce that are used by people in Indonesia, one of which is the TikTok Shop. TikTok and TikTok Shop are combined into one application, in which TikTok Shop is a business platform published by TikTok to make it easy for users who want to buy or sell a product. The purpose of this study was to determine and analyze the effect of Electronic Word of Mouth, price, and ease of use simultaneously on purchasing decisions at social commerce TikTok Shop. The population in this study were active students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019-2020 who had purchased at the TikTok Shop. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 100 respondents. The results showed that partially, price and ease of use had a significant effect on purchasing decisions, while electronic word of mouth had no significant effect on purchasing decisions. Simultaneously, electronic word of mouth, price, and ease of use have a significant effect on purchasing decisions. Keyword: Electronic Word of Mouth, Price, Ease of Use, purchasing decision